2019
DOI: 10.1186/s41240-019-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzymatically hydrolyzed fish by-products in diet of juvenile rainbow trout (Oncorhynchus mykiss)

Abstract: Five experimental diets were formulated to evaluate the effects of dietary enzymatically hydrolyzed tuna by-product on growth, non-specific immune responses, and hematology of juvenile rainbow trout (Oncorhynchus mykiss). A basal diet with 50% of fishmeal was used as control (CON) and four other diets replaced 12.5% (TBB 12.5 ), 25% (TBB 25 ), 37.5% (TBB 37.5 ), and 50% (TBB 50 ) of fish meal in the CON diet. Juvenile rainbow trout (4.87 ± 0.05 g) were randomly distributed into 15 tanks (50 L) and fed 3-4% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…Better digestive enzymatic activities were found in the ECP1 group which has the better growth WGR and PER. Similar results were observed in juvenile rainbow trout (Oncorhynchus mykiss) [26], Pacific white shrimp [27], European seabass (Dicentrarchus labrax) [28], and tilapia (Oreochromis niloticus) [29] fed enzymatic fish by-products, feather-enzymatic hydrolysates, enzymatically hydrolysed aquaculture by-products, and enzymatic poultry by-products, respectively. Poultry and fish by-products have been considered suitable ingredients in the diet of aquatic animals due to their high nutritional characteristics [30].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Better digestive enzymatic activities were found in the ECP1 group which has the better growth WGR and PER. Similar results were observed in juvenile rainbow trout (Oncorhynchus mykiss) [26], Pacific white shrimp [27], European seabass (Dicentrarchus labrax) [28], and tilapia (Oreochromis niloticus) [29] fed enzymatic fish by-products, feather-enzymatic hydrolysates, enzymatically hydrolysed aquaculture by-products, and enzymatic poultry by-products, respectively. Poultry and fish by-products have been considered suitable ingredients in the diet of aquatic animals due to their high nutritional characteristics [30].…”
Section: Discussionsupporting
confidence: 78%
“…VSI, HSI, and CF are good representatives of general wellbeing, health, and feed quality in aquatic organisms [34]. Like juvenile rainbow trout (Oncorhynchus mykiss) and genetically improved tilapia fed enzymatic fish by-product and enzymatic chicken liver, respectively [26,29], there was no significant difference observed in VSI, HSI, and CF between the groups in this study. Dietary and environmental factors may have contributed to the variations in whole-body composition [31,35].…”
Section: Discussionmentioning
confidence: 61%
“…(2018) found that RBT and myeloperoxidase activity could be influenced by the supplementation of shrimp, tilapia and krill hydrolysates into the low FM diets. On the other hand, the antioxidant indicators like SOD and catalase are involved in the main antioxidant defence system by removing and detoxifying oxygen radicals generated within the cells under normal or stressful conditions (Bae et al., 2019). In our study, GIFT Tilapia fed the hydrolysate‐supplemented diets showed improved antioxidant status with increased SOD and catalase levels, thus paving the way for easy acceptance by consumer.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolysis enzyme can eliminate the excess crude fiber content and anti-nutrient compounds (tannins and phytic acid) on bran, wheat, rice plants, and seeds (Dhingra et al, 2012;Raveendran et al, 2018). This particular process is possible to improve the nutritive value of each feed ingredients (Bae et al, 2019). This condition is also expected to have similar effect in I. zollingeriana leaf meal.…”
Section: Introductionmentioning
confidence: 99%